Analysis of Factors Affecting the Intention to Use the DANA Application in Lombok Based on the TAM Model - Kaspul Anwar (Journal of Islamic Financial Technology, 2025)
This study aims to analyze the factors that affect the intention to use DANA e-wallets using the SEM-PLS method. The evaluation of the measurement model is carried out through Convergent Validity, and Discriminant Validity tests to ensure that the research instrument is valid and reliable. The bootstrapping test was used to assess the significance of the relationship between latent variables based on a t-statistic value with a t-> limit of 1.96 at a significance level of 5%. Data was obtained through a questionnaire of 130 respondents who were selected using purposive sampling with the criteria of being at least 17 years old, domiciled in East Lombok, understood the DANA application, and had the intention to use it, and supported by secondary data from various scientific sources. The results of the study show that the variables in the model have a different influence on the intention of using the DANA application. Perceived Usefulness had no significant effect on usage intent (t = 1.676; p = 0.094), while Perceived Ease of Use was proven to have a positive and significant effect (t = 2.533; p = 0.011), so the easier the application is to use, the higher the user's intention to use it. In addition, Perceived Security also had a positive and significant effect (t = 3,039; p = 0.002), confirming that the higher the sense of security that users feel, the greater their tendency to continue using DANA. These findings provide an empirical overview of the factors of digital financial service acceptance in the Lombok community. Keywords: Intent To Use, E-Wallet, DANA, SEM-PLS, Financial Technology